Individual preference towards islamic mutual fund / Siti Humairah Shahrir and Syahril Azri Ahamad Tarmazi - Shahrir, Siti Humairah; Ahamad Tarmazi, Syahril Azri (2014)
Islamic Mutual Fund in Malaysia have experienced phenomenal growth in the past few years. This growth reflects the suitability of collective investment in Malaysia. Islamic Mutual Fund forms an important part of the Malaysian economic nowadays. Eventhough growth of Islamic Mutual Fund are still lack behind Conventional Mutual Fund, however the demand and growth of Islamic Mutual Fund are keep on increase year by year. The aim of this study is to determine the individual preference towards Islamic Mutual Funds in Shah Alam. The independent variable that researcher have been used was Shariah compliant, market risk and growth. About one hundred questionnaire were distributed and eight nine useable questionnaire have been collected back. Resercher gives the questionnare to the public that lives in Shah Alam as a sample in this study. The design of the questionnaire is focus on Likert Scale to know the level of understanding on how strongly agree or strongly disagree of the respondent with the statement regarding the principles. As a conclusion, this study gets the appropriate data to measure the individual preference towards Islamic Mutual Fund.